Apoptosis induction in human leukemic promyelocytic HL-60 and monocytic U937 cell lines by Goniothalamin - Ploingarm Petsophonsakul (2018)
Goniothalamin is an active compound extracted from Goniothalamus griffithii, a local plant found in northern Thailand. Goniothalamin inhibits cancer cell growth but is also toxic to normal cells. The aims of this study were to identify the cytotoxic effect of goniothalamin and the mechanism of cell death in human HL-60 and U937 cells. Cytotoxicity was determined by MTT assay and cell cycle profiles were demonstrated by staining with propidium iodide (PI) and flow cytometry. Apoptosis was confirmed by staining with annexin V-FITC/propidium iodide (PI) and flow cytometry. Reduction of mitochondrial transmembrane potential was determined by staining with dihexyloxacarbocyanine iodide and flow cytometry and expression of Smac, caspase-8 and -9 was demonstrated by Western blotting. Goniothalamin inhibited growth of HL-60 and U937 cell lines. An increase of SubG1 phase was found in their cell cycle profiles, indicating apoptosis as the mode of cell death. Apoptosis was confirmed by the flip-flop of phosphatidylserine using annexin V-FITC/PI assay in HL60 and U937 cells in a dose response manner. Furthermore, reduction of mitochondrial transmembrane potential was found in both cell types while expression of caspase-8, -9 and Smac/Diablo was increased in HL-60 cells. Taken together, our results indicate that goniothalamin-treated human leukemic cells undergo apoptosis via intrinsic and extrinsic pathways.